Solicitação de endoscopia baseada em “sinais de alerta” para o diagnóstico de câncer gástrico: qual é a verdadeira acurácia? - CARVALHO, Alan Goes de (2024)
Gastric cancer is a type of neoplasia with a high global incidence and a low survival rate in more advanced cases. With nonspecific symptoms, its diagnosis is often delayed, resulting in an unfavorable prognosis. Although the "warning signs" for this type of cancer – anemia, gastrointestinal bleeding, palpable abdominal mass, dysphagia, weight loss, persistent vomiting, and age over 50 – may indicate malignancy, their diagnostic effectiveness is questioned. In Brazil, especially in the Northern region where the incidence is notable, requesting endoscopy based on such signs lacks confirmation. This study aims to evaluate the accuracy of endoscopy based on "warning signs" in detecting gastric cancer, contributing to more efficient screening and a better understanding of the disease. For this purpose, a case control study was conducted between August 2022 and June 2023 in the endoscopy department of João de Barros Barreto University Hospital (HUJBB), where a questionnaire was administered to the patients. The "cases" group consisted of 36 patients with a confirmed diagnosis of gastric neoplasia, while the "control" group included 252 patients with dyspeptic symptoms but without cancer. Data analysis revealed that the majority of patients were located in Belém, with a predominance of female patients (58.7%). The average age was 53.1 years, and the presence of warning signs averaged 1.8 per patient. The main warning signs related to gastric cancer were age over 50, weight loss, absence of bleeding, and absence of anemia. The association with these last two warning signs contradicts the literature, and non-ulcer dyspepsia also showed a relationship with the absence of anemia, as did peptic ulcer disease, which was associated with weight loss, indicating an overlap of warning signs both in gastric cancer and in the absence of this diagnosis. These findings may indicate that the strategy of requesting endoscopy based on warning signs is not appropriate. The warning signs traditionally listed in the literature did not show adequate accuracy for detecting gastric cancer, highlighting the need for more comprehensive research to support decision-making strategies regarding the request for endoscopy and early diagnosis of neoplasia.